The Urgency of Customer Personal Data Protection in Digital Banking - Nasution, Alvin Hamzah (Rechtsvinding, 2025)
The development of digital technology in the financial sector has transformed banking services to be more open, fast, and data-driven. On the other hand, the increasing intensity of processing customers' personal data also poses new challenges related to the protection of privacy rights. This study aims to examine the urgency of legal protection for customers' personal data in Indonesia's digital financial ecosystem. The method used is a normative legal approach with an analysis of regulations such as Law Number 27 of 2022 concerning Personal Data Protection and POJK No. 6/POJK.07/2022. The results of the study show that although Indonesia already has a formal legal framework, its implementation still faces obstacles such as the absence of a data supervisory authority, low digital legal literacy among the public, and weak enforcement of sanctions. Therefore, a holistic approach is needed in the form of strengthening regulations, public education, and harmonization with international standards to guarantee customer rights and build a safe and sustainable digital financial industry.